KNOWLEDGE AND CONSIDER THE PREVALENCE AND MANAGEMENT OF PEDIATRIC ASTHMA - Dalal Mohammed Ameen Zainy; Manal Ali Hasan Albakle; Fareed Riyadh Hashim Alhamadani (Scholar Express Journals, 2021)
A study focuses on Knowledge and Consider the Prevalence and Management of Pediatric Asthma Where 88 children were collected from Karbala Teaching Hospital for Children, Karbala, Iraq, and the average ages of the children ranged from 3 to 10 years were divided into two categories. Where it was relied on the SPSS 25 soft program to analyze all the information and statistical data to clarify the exact details of the specifications and results of pediatric patients The results reached the following: The highest age value for asthmatic patients was recorded at 7 years and 10 years Asthma detection and treatment rates are not high enough, and untreated asthmatics can develop sleep disturbances, daytime fatigue and decreased concentration. People with asthma and their families can drop out of school and work, with financial implications for their families and society. If symptoms are severe, people with asthma may need urgent medical attention and be admitted to the hospital for treatment and monitoring. In severe cases, asthma can be fatal.
Keywords: Symptoms; Asthma; Pediatric; WHO